Influence of hand net mesh type and sex on experimental infection with Aeromonas hydrophila in Brazilian native fish Astyanax altiparanae - Alvarez-Rubio, Norquis Caled [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Cala-Delgado, Daniel L. [UNESP]; Cueva Quiroz, Victor Alexander [UNESP]; Miani Verri, Bruno Luis [UNESP]; Ramos Espinoza, Fernando Carlos [UNESP]; de Moraes, Julieta Rodini Engrácia [UNESP] (Elsevier, 2020)
Farmed fish are permanently exposed to management procedures such as netting that can result in stress, skin injuries and subsequent secondary infections. The type of mesh material can modulate the magnitude of netting injury, yet there is scarce information on this topic for aquaculture species. The aim of this study was to evaluate the influence of net material on experimental infection by Aeromonas hydrophila using male and female Astyanax altiparanae, yellowtail tetra, as an infection model. Two hundred and fifty six A. altiparanae were distributed into 16 groups considering sex, types of net material (nylon, polypropylene, polyethylene, and a control group handled without net), and immersion challenge with A. hydrophila. Prior to infection, fish were anesthetized and submitted to netting for 30 s. Immediately, a fluorescein bath was applied under UV light to detect skin lesions. Later, fish were infected by immersion challenge in diluted bacterial solution, while control groups were immersed in sterile PBS. It was verified that the fish handled with nylon net mesh showed more extensive lesions than groups handled with polypropylene and polyethylene nets. Survival after infection was significantly lower in fish previously handled with nylon net when compared to all other groups, while no differences were found between polypropylene, polyethylene nets or fish handled by hand. There was no gender influence on lesions or mortality. It was concluded that yellowtail tetra is sensitive to netting and polypropylene and polyethylene capture nets should be used for handling this species. Additionally, nylon hand nets should be banned to avoid injuries that could serve as gateways for opportunist pathogens such as A. hydrophila
Keywords: Aeromonosis; Bacterial infection; Fluorescein; Lambari; Native fish